Frog in the well : portraits of Japan by Watanabe Kazan, 1793-1841 - Keene, Donald (Asia perspectives., 2006)
Frog in the Well is a vivid and revealing account of Watanabe Kazan, one of the most important intellectuals of the late Tokugawa period. From his impoverished upbringing to his tragic suicide in exile, Kazan's life and work reflected a turbulent period in Japan's history. He was a famous artist, a Confucian scholar, a student of Western culture, a samurai, and a critic of the shogunate who, nevertheless, felt compelled to kill himself for fear that he had caused his lord anxiety. During this period, a typical Japanese scholar or artist refused to acknowledge the outside.